2016
DOI: 10.1186/s40064-016-2066-z
|View full text |Cite
|
Sign up to set email alerts
|

The count of tender rather than swollen joints correlates with aortic stiffness in patients with rheumatoid arthritis

Abstract: BackgroundPatients with rheumatoid arthritis (RA) are at a higher cardiovascular (CV) risk in comparison to the general population. CV risk associates closely with aortic stiffness. Aim of this exploration was therefore to evaluate aortic stiffness in patients with RA and to examine its association with various RA associated parameters as well as with traditional CV risk factors.MethodsMeasurements of carotid-femoral pulse wave velocity (cfPWV) were analyzed retrospectively in 38 RA patients and 25 controls. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Эпидемиологические исследования дают основания считать, что одним из основных факторов может быть воспалительная активность, однако механизмы, лежащие в основе, остаются неясными. В нашей работе произведен анализ изменений артериального русла у пациентов с РА без анамнеза больших сердечно-сосуди- [22][23][24][25][26][27][28]. Нами показано, что маркеры артериальной ригидности в данной популяции встречаются в 2 раза чаще маркеров атеросклероза, при этом наиболее ранним маркером можно считать изменение градиента жесткости, которое встречается более чем у половины пациентов с РА, в том числе и при нормальных значениях кфСРПВ.…”
Section: Discussionunclassified
“…Эпидемиологические исследования дают основания считать, что одним из основных факторов может быть воспалительная активность, однако механизмы, лежащие в основе, остаются неясными. В нашей работе произведен анализ изменений артериального русла у пациентов с РА без анамнеза больших сердечно-сосуди- [22][23][24][25][26][27][28]. Нами показано, что маркеры артериальной ригидности в данной популяции встречаются в 2 раза чаще маркеров атеросклероза, при этом наиболее ранним маркером можно считать изменение градиента жесткости, которое встречается более чем у половины пациентов с РА, в том числе и при нормальных значениях кфСРПВ.…”
Section: Discussionunclassified
“…Two studies studies assessed the relationship between serum lipids and arterial stiffness in RA patients, they found that hyperlipidemia did not significantly correlate with aortic stiffness as measured by carotid femoral pulse wave velocity (cfPWV). 27 , 28 But when the components of the lipids were considered separately, aortic stiffness showed direct associations only with triglycerides. 29 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PWV is increased in these patients and that there is an association with age, disease duration, and erythrocyte sedimentation rate (ESR) ( 17 ). Our research group could examine PWV during the last few years in patients with various autoimmune rheumatic diseases, such as rheumatoid arthritis ( 8 ), mixed connective tissue disease (MCTD) ( 7 ), systemic lupus erythematosus (SLE) ( 10 ), and antisynthetase syndrome (ASyS) ( 11 ). In the case of MCTD and ASyS, aortic PWV was statistically significantly higher in comparison to respective control groups even after adjustment for possible confounding factors.…”
Section: Cvd Surrogate Markersmentioning
confidence: 99%
“…Furthermore, it is expected that a part of the two-fold higher risk of heart failure and total mortality in RA may be due to myocardial disease associated with inflammation including elevated acute phase proteins, T-Cell subsets, proinflammatory cytokines and the presence of circulating auto-antibodies (5). Autoimmune rheumatic diseases are known to affect the valves, myocardium, pericardium as well as the cardiac vasculature and conduction system, leading to multiple cardiovascular manifestations that in some cases can remain clinically silent or lead to a considerable cardiovascular mortality and morbidity (6)(7)(8)(9)(10). Atherosclerosis plays a substantial role in CVD morbidity and mortality; the degree of coronary atherosclerosis observed in patients with rheumatic diseases can be as accelerated, diffuse, and extensive as in patients with diabetes mellitus (11).…”
Section: Introductionmentioning
confidence: 99%